Researching tutors’ perceptions of effective online pedagogy: The Learning Activity Analysis Tool - Joyes, Gordon (Proceedings of the International Conference on Networked Learning, 2008)
The tutor plays an important role in mediating online learning and behaviour is influenced by their understandings of effective pedagogy. An understanding of the relationship between pedagogic beliefs/ understandings and actual practice is therefore a key research area. However research into these understandings is problematic as there are apparent differences between espoused beliefs about teaching and learning and actual practice or enacted beliefs. Measurement and research design/instrument issues can account for part of the disagreements between these. It can be argued that differing abilities to reflect on personal pedagogic practice as well as the diverse pedagogic language used by different lecturers and subject disciplines could also account for these differences. This paper explores the use of an online tool for researching online tutors understandings of effective practice by focusing on an analysis of an existing online learning activity and tutors’ views about the nature of the learner support that might be needed. The context for the study is the eEducator project within the UK government funded e-learning International Sino-UK programme. This involved collaboration between the University of Nottingham, UK and Beijing Foreign Studies University, China to develop a module for training tutors of online learners - one that could be adapted for use in a variety of contexts. As part of this project a reflective analytic online tool the Learning Activity Analaysis Tool (LAAT) was developed and this is the focus of the paper. The module was piloted at the School of Distance Education, Universiti Sains Malaysia, Penang. Six experienced tutors of undergraduate distance learners from different subject disciplines, teacher education, mathematics, biology, chemistry and English as a second language participated in the use of the LAAT. Each tutor analysed the same online learning activity and provided an online summary of the strategies they would use to support the online learners. They then shared their analyses using the functionality built into the LAAT. An asynchronous online discussion followed that was used to explore the ways the LAAT could be used to explore the tutors pedagogic understandings. The research involved an initial analysis of the LAAT entries to reveal the pedagogic understandings underpinning the tutor’s strategies for learner support. This was followed by discussion group questions designed to explore instances of actual practice. This research revealed a sequence of activities that acts as a model for developing pedagogic understanding using the LAAT. The strength of the LAAT in this context is that it ensures a holistic approach to analysing the nature of the support learners may need in relation to an online learning activity. The implications for supporting effective networked learning are self-evident in that the LAAT encourages an analytic and enquiry based approach to developing effective learning environments. It is particularly helpful when considering activities that involve online communities of learners working within course based education where the elements of regulations and of roles play an important part in ensuring successful engagement in the learning process. The LAAT allows the supporting tutor/s to think through the design of the networked learning activity before it starts and predict points of tension and explore strategies to overcome these. However the underlying pedagogic implications of these strategies need to be considered if new pedagogic perspectives are to be developed and this can only be achieved by taking a broader view of the nature of the learner and of learning. This limitation might be viewed as a limitation of Activity Theory itself and the ways it focuses on a specific activity. However third generation activity theory provides a framework to focus on multiple, interrelated activity systems which would reveal the broader pedagogic issues.